Multipion Bose-Einstein correlations in pp,p-Pb, and Pb-Pb collisions at energies available at the CERN Large Hadron Collider - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Danisch, Meike; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review, 2016)
Three- and four-pion Bose-Einstein correlations are presented in pp,p-Pb, and Pb-Pb collisions at the LHC. We compare our measured four-pion correlations to the expectation derived from two- and three-pion measurements. Such a comparison provides a method to search for coherent pion emission. We also present mixed-charge correlations in order to demonstrate the effectiveness of several analysis procedures such as Coulomb corrections. Same-charge four-pion correlations in pp and p-Pb appear consistent with the expectations from three-pion measurements. However, the presence of non-negligible background correlations in both systems prevent a conclusive statement. In Pb-Pb collisions, we observe a significant suppression of three- and four-pion Bose-Einstein correlations compared to expectations from two-pion measurements. There appears to be no centrality dependence of the suppression within the 0%-50% centrality interval. The origin of the suppression is not clear. However, by postulating either coherent pion emission or large multibody Coulomb effects, the suppression may be explained.